Environmentally benign enhanced H-2 production from abundant copious waste H2S using size tuneable cubic bismuth (Bi-0) quantum dots-GeO2 glass photocatalyst under solar light - Apte, Sanjay K.; Garaje, Sunil N.; Naik, Sonali D.; Waichal, Rupali P.; Kale, Bharat B. (Green Chemistry, 2013)
Hydrogen sulfide is a copious gas produced in refineries (15-20%) as well as billions of tons produced as a by-product in alkali industries. Selectively, only 5% has been utilised for the Claus process to produce liquid sulfur and it is also well known for its uneconomical and environmental problems. Here, we have demonstrated a significant green approach for conversion of poisonous H2S into H-2 by stable cubic bismuth (Bi-0) quantum dot-glass nanosystems using solar light as the energy source. Previously, metal oxides and sulfides have been demonstrated as solar light photocatalysts. However, a unique bismuth quantum dot-glass nanosystem has been designed where cubic phase bismuth quantum dots of size 1-2 nm are grown in the germanate glass matrix successfully. The presence of bismuth (Bi-0) was confirmed by XRD, Raman, TEM and X-ray photoelectron spectroscopy (XPS). The glass nanosystem shows quantum confinement with variation of the band gap from 2.95-1.51 eV. Considering the broad absorption from visible to near IR, we used this glass nanosystem as a solar light active photocatalyst and hydrogen production with respect to the quantum confinement of bismuth (Bi-0) quantum dots has been demonstrated for the first time. The photocatalytic activity for hydrogen production using glass nano-systems having bismuth quantum dot sizes of 1-2 nm and 3-6 nm was measured under solar light and prima fascia observations revealed that the glass nanosystems with very small quantum dots (1-2 nm) showed enhanced hydrogen evolution (11 541 mu mol h(-1) g(-1)) from H2S. The hydrogen evolution obtained is much higher than for previously reported visible light active nanostructured sulfide/oxide or embedded glass nanosystems. The glass nanosystems were also used for water splitting and show evolution of hydrogen without any co-catalyst. It is noteworthy that the quantum dot-glass photocatalyst is highly stable and catalyst regeneration is quite easy and fast. Hence, the QD-bismuth-glass nanocomposites have significant advantages over normal nanosized powder catalysts. Such unique glass nanosystems will also have great potential in photonics and optoelectronic applications.